Enhanced gain saturation model of nonlinear semiconductor optical amplifiers - Kharraz, Osayd M.; Mohd Supa'at, Abu Sahmah; Atieh, Muataz Ali; Abdul Kadir@Jaafar, Muhammad Zamzuri (Institution of Engineering and Technology (IET), 2018)
This paper proposes an enhanced gain saturation model of nonlinear semiconductor optical amplifiers (SOAs) by incorporating material-dependent gain compression factor. The rate equations are utilized with the extra gain compression term for Indium-Gallium-Arsenide material-based SOA to account for the steep relaxation oscillations behaviour of nonlinear SOAs. The proposed gain saturation model is verified with experimental results that showed very good agreements with mean square error of 0.094